Neutronic modelling of nanofluids as a primary coolant in VVER-440 reactor using the Serpent 2 Monte Carlo code. (March 2019) - Abdullah, H; Smirnov, A D; Tikhomirov, G V
Abstract: The nanofluids as an engineered fluid offer a large enhancement in heat transfer, in particular for boiling heat transfer and critical heat flux. These features lead to increase the power density of the nuclear reactor. In this paper, we investigate the neutronic simulation of nanofluids as a primary coolant in VVER-440 reactor and study the availability of using it without changing the system characteristics. The analysis of nanofluid fuel assembly is performed by using Serpent code. As a result of changing effective multiplication factor of the six types of nanoparticles which have been studied extensively for their heat transfer prosperities and absorption cross sections including Al2 O3, Si, Zr, TiO2, CuO, and Ti with different volume fractions, it can be concluded the optimum nanoparticles are alumina at concentration 0.01 volume fraction.